A literature review on the effects of failure in the English subject in national grade 12 examinations on Cambodian students - Oeun, Saem; Heng, Kimkong (Journal of Research on English and Language Learning (J-REaLL), 2024)
English plays a pivotal role in high-stakes examinations at both national and international contexts. This review article aims to discuss the effects of failure in the English subject in the national grade 12 examinations on Cambodian students. Drawing on secondary sources such as journal articles, conference papers, theses and dissertations, official documents or research reports, books, book chapters, and newspaper articles, the article highlights a number of effects of students’ failure in national high school exams in general contexts, such as (a) increased school dropouts, (b) limited higher education enrolment, (c) limited job opportunities, and (d) compromised psychological well-being. The article also identifies several effects of failure in the English subject in national grade 12 examinations on Cambodian students. These include effects on (a) educational opportunities, (b) job opportunities, (c) communication ability, and (d) psychological well-being. The article provides some recommendations to help students who fail the English subject in the national exam deal with the consequences after exam failure. The recommendations focus on the roles of various stakeholders in general education in Cambodia, such as the Ministry of Education, Youth, and Sport (MoEYS), teachers, parents, students, and other relevant stakeholders. The article concludes with some suggestions for future research.